The Influence of the European Foundation Model for Quality Management (EFQM) in the Behavior of User Complaints from Banco de la Nación ATMs in Metropolitan Lima in the Period 2019 - Quintanilla Gómez, Juan Carlos (2022)
This article is developed based on the quality problem in the most demanded service channel at the national level of the Banco de la Nación de Peru, it is Multired ATMs, proposing as an alternative solution the application of the European Foundation Model for Quality Management (EFQM). This model was applied taking as a reference the current state of ATMs in Metropolitan Lima. The European Foundation Model for Quality Management (EFQM) is based on the purpose, vision, strategy, organizational culture, leadership, involving stakeholders, creating sustainable value, managing the operation and transformation, stakeholder perception, and strategic and operational performance. Through this study, the influence of the model on the behavior of claims was verified, increasing the degree of user satisfaction and allowing the impact of quality management on continuous improvement to be determined.